2022
DOI: 10.2478/johh-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of compost amendments to soil on soil structure, hydraulic properties, and water regime

Abstract: Despite the increasing interest in applying composts as soil amendments worldwide, there is a lack of knowledge on short-term effects of compost amendments on soil structural and hydraulic properties. Our goal was to study the effect of compost and vermicompost-based soil amendments on soil structure, soil water retention characteristics, aggregate stability and plant water use efficiency compared to that of mineral fertilizers and food-waste digestate and examine if these effects are evident within a short ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 68 publications
2
20
0
1
Order By: Relevance
“…Rivier et al also reported an increased FD with manure application which was similar to our ndings in the Brookings site, where the application of medium manure increased FD as compared to medium fertilizer treatments at 20 to 30 cm soil depth 32 . A higher FD can be due to the more complex pore structure of the soils 33 and this can contribute to the soil fertility 34 .…”
supporting
confidence: 89%
“…Rivier et al also reported an increased FD with manure application which was similar to our ndings in the Brookings site, where the application of medium manure increased FD as compared to medium fertilizer treatments at 20 to 30 cm soil depth 32 . A higher FD can be due to the more complex pore structure of the soils 33 and this can contribute to the soil fertility 34 .…”
supporting
confidence: 89%
“…Therefore, using zerokilometer compost may represent an agronomic practice to be suggested, especially when combined with other agroecological techniques [7,8]. It is well known that adding compost to soil improves the physical and hydraulic characteristics of the porous medium, including bulk density or porosity, water retention, and hydraulic conductivity (among others, e.g, [9][10][11]). For instance, Glab et al [12] reported the effects of the addition of different co-composted maize, sewage sludge, and biochar mixtures on the physical properties of a sandy soil.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the long-term effects of compost addition to soil have been extensively investigated [14], and some studies have sporadically investigated the effects on structural stability in the medium term, namely, two-three years after amendments [15,16]. Rivier et al [11], for example, pointed out that of the approximately six hundred articles published on the topic of compost use, only about 10% of them focused on evaluating the impact on soil structure and changes in hydraulic properties [17]. Furthermore, the short-or medium-term effect is largely underrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…Another point that requires further investigation is the use of repacked soil samples that could be non-representative of field conditions. Many researchers hypothesized that incorporation of compost would influence soil structure and, consequently, soil hydraulic properties in the short term (among others, [1,22]). The addition of compost to sieved soil, to obtain a repacked laboratory sample, can be likened, to some extent, to the real soil shortly after compost incorporation followed by tillage.…”
Section: Influence Of Compost Amendment On Soil Water Retention and P...mentioning
confidence: 99%
“…Compared with the control soil, the physical properties of the amended soil were significantly improved with beneficial effects that were dependent on the rate of compost application and the type of feedstock. Likewise, Rivier et al [22] investigated the effect of compost and vermicompost on soil structure, water retention, aggregate stability, and plant water use efficiency, compared with that of mineral fertilizers and food-waste digestate.…”
Section: Introductionmentioning
confidence: 99%